KJ Fashion Shoes E-Commerce Mobile-Based Application with Implementation of Image Recognition System - Soh, Kai Jie (2022)
Nowadays, the e-commerce mobile application is famous, and everyone had heard of and used it before. However, in this project, the focus field is fashion shoes. But some of the fashion shoes e-commerce does not apply the implementation of an image recognition system that able the user to visual search such as searching with the image without typing any keyword. Hence the purpose of this project is to implement the image recognition system in fashion shoes e-commerce to let the user find their preferred product more quickly and easily. After the research is done on three existing applications, we can find that there has a unique feature that makes it easy for the user. Indeed, the proposed application will also have a unique feature that reduces the time-consuming of the user for searching a product. The Agile methodology is applied for this proposed application by step by step which undergo of Define phase, Design phase, Test phase, and Deploy phase to do the implementation. Furthermore, the User Acceptance Test will also be conducted to ensure the application can run without any errors.